Koromu (Kesawai) grammar and information structure of a New Guinea language - Priestley, Carol (Pacific linguistics., 2019)
This book is a grammatical description of Koromu (or Kesawai), an endangered and previously undescribed language in Papua New Guinea's Ramu Valley. Koromu belongs to the Madang subgroup of the putative Trans New Guinea family. The grammar covers the structures of the language, with an emphasis on information structure. Geographic, linguistic, social and historical setting are described as well as phonology and morphophonology. The book examines the morphosyntactic structures of the language, covering basic clause structure, word classes, phrase structures and structures of spatial reference, verbal morphology, serial verb constructions, experiencer object constructions and the various constructions of clause combining (clause chaining, complement clauses, adverbial and relative clauses). Chapters also deal with noun phrase (non)realisation and morphological signaling of prominence and show how links and tails are encoded grammatically. Appendices contain texts and a wordlist.